Prospective analysis of injury demographics, distribution, severity and risk factors in adolescent climbers - Schöffl, V. R.; Schöffl, I.; Jones, G.; Klinder, A.; Küpper, T.; Gunselmann, L.; Simon, M.; Moser, O.; Bayer, T.; Lutter, C. (BMJ Open Sport & Exercise Medicine, 2025)
Objective This study aims to prospectively analyse current demographics, distribution and severity of climbing injuries in adolescents. We hypothesised that the injury distribution of adolescent climbers would differ from adults, as presented in the literature and that primary periphyseal stress injuries of the finger (PPSI) will be very common and correlate with training hours and climbing level.